(untitled) (Journal of Hama University, 2023)
The study aimed to build the experiences and activities depended on discussion strategies to developing citizenship for children, and to achieve the goal of the study, a list for training needs for affiliation appreciation of kindergarten, concepts of citizenship was built in the light of four domains and twenty eight sub Lind, and four activities was built on discussion strategies to developing citizenship for children, The study has used the experimental method, and a sample of (15) males and females- whose ages range between 5 to 6 have been chosen. The study was applied in the first semester of the academic year 20200-2023, the results of the study showed the following: there are no differences of statistic meanings between the average of- males and females-in the experimental group on the standard of national experiences. But there are differences of statistic interpretation between children’s average grades in the experimental and standardizing in favors of the experimental one. One of the most important suggestions of this study is exploiting children’s love in narrating the past accomplishments of home land